2022
DOI: 10.1007/s00436-022-07695-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimated specific antibody-based true sero-prevalences of canine filariosis in dogs in Central Europe and the UK

Abstract: Dirofilariosis is a vector-borne disease mainly caused by Dirofilaria immitis and Dirofilaria repens. In contrast to the known endemicity of dirofilariosis in southern and south-eastern Europe, information on the distribution of D. repens in Central-Europe is fragmentary. We tested 8877 serum samples from dogs from Austria, Denmark, Germany, Italy, Lithuania, Poland, Switzerland and the UK using an ELISA detecting filarial-specific antibodies, hypothesising higher occurrence of D. repens. Based on two overlapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Thus, pets travelling from or to the United Kingdom may be subject to differing health requirements compared to EU countries ( 54 , 55 ). During the first epidemiological survey conducted in 2010, the filarial-specific antibody prevalence was recorded as 0% over a total of 1,028 dogs tested across the United Kingdom ( 56 ). A later European study performed between 2016 and 2020 revealed a canine HW seroprevalence of 5–7% in central/southern England, with no seropositive dogs detected in other parts of the country ( 57 ).…”
Section: Dirofilaria Spp Infections In the United Kingdom: T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, pets travelling from or to the United Kingdom may be subject to differing health requirements compared to EU countries ( 54 , 55 ). During the first epidemiological survey conducted in 2010, the filarial-specific antibody prevalence was recorded as 0% over a total of 1,028 dogs tested across the United Kingdom ( 56 ). A later European study performed between 2016 and 2020 revealed a canine HW seroprevalence of 5–7% in central/southern England, with no seropositive dogs detected in other parts of the country ( 57 ).…”
Section: Dirofilaria Spp Infections In the United Kingdom: T...mentioning
confidence: 99%
“…A later European study performed between 2016 and 2020 revealed a canine HW seroprevalence of 5–7% in central/southern England, with no seropositive dogs detected in other parts of the country ( 57 ). While the overall seroprevalence of HW infection remains very low ( 56 , 57 ), there have been two reports of clinical D. repens infection in United Kingdom dogs in recent years in the midlands of England ( 12 , 58 , 59 ). Both studies reported infection in imported dogs, the first originating from Romania ( 59 , 60 ) and the second from Corfu ( 58 ).…”
Section: Dirofilaria Spp Infections In the United Kingdom: T...mentioning
confidence: 99%
“…Both bacteria infect the tick through the feeding [7] and can infect new subjects when ticks molt and bite again a new host or pass to a new tick generation by trans-ovarian transmission. Dirofilaria immitis is one nematode transmitted by several species [8] of mosquitoes [9] from genera Culex, Aedes, Anopheles and Ochlerotatus. All filaria have filiform elongated body.…”
Section: Introductionmentioning
confidence: 99%